(untitled) (Raparin Journal of Humanities (RJH), 2020)
This study is structured into four chapters; the first is an introduction part that includes aims, objectives, limitation, and concepts of the research. The second will be on the theoretical framework which contains the concept of manager, its rolls and roll of manger in modern studying systems; it also concentrates on three researches as a brief literature review on the topic of this paper. Then, it moves on to the methodological chapter. The fourth chapter discusses and describes the findings, restates and summarises the results from the research process. This research aims at conducting the teachers’ perceptions about the role of managers upon developing the teaching process in the basic schools of Sulaymanyah (2019 - 2020). Based on the study aims, the researchers relied on a descriptive manner. The research sample concluded all teachers from both eastern and western education directorate of Sulaymanyah. The sample size set as (185) of all teachers from both education directorates which are (1246) teachers. Based on the literature review, a close-ended questionnaire is chosen as a suitable approach to collect data among participants, in addition, 52 questions were prepared and divided by over four clauses such as (management system, teacher developments, student developments, and relatives’ side of students. After the prepared questionnaire, validity was assessed by experts and it was (0.81). Then, for the purpose of the research reliability, the questionnaire was repeated upon participants and it was resulted (0.84) using Person ،Correlation Coefficient. Furthermore, in order to analysing collected data, present a meaningful result and discus detailed findings, this study benefitted from many statistical tests including (weight variation test means, arithmetic average (using SPSS. Finally, it was reached to a set of conclusions, including the role of managers was positive in three aspects in managing, developing teachers’ ability and related sides of student relatives). On the other, their roles were negative on developing students. Another result was that there was no different opinion among teachers from both eastern and western education directorates.